Kurt Vonnegut drawings - Vonnegut, Kurt 1922-2007 (Monacelli Press, 2014)
Those who know Kurt Vonnegut as one of America's most beloved and influential writers will be surprised and delighted to discover that he was also a gifted graphic artist. This book brings together the finest examples of his funny, strange, and moving drawings